Development of Sun Screen Gel Formulation from Secang Wood Extract (Caesalpinia sappan L.) - Wahidin Wahidin; Hasnaeni Hasnaeni; Nurmaya Effendi (SEAN Institute, 2026)
Exposure to ultraviolet (UV) radiation can cause oxidative stress, premature aging, and even skin cancer, so it is necessary to develop sunscreens based on natural ingredients that are safe and effective. Secang wood (Caesalpinia sappan L.) is known to contain phenolic compounds and brazilin which have antioxidant activity and have the potential as photoprotective agents. This study aims to develop a sunscreen gel formulation from ethanol extract of secang wood and evaluate its antioxidant activity, Sun Protection Factor (SPF) value, physical characteristics, and stability. Extraction was carried out using the maceration method using 96% ethanol. Antioxidant activity was determined using the DPPH method, while sunscreen activity was analyzed in vitro using UV-Vis spectrophotometry with the Mansur method. The gel was formulated in four formulas with varying extract concentrations (0.85% and 1.7%) and Carbopol (0.75% and 1%). Evaluation of the preparation included organoleptic tests, homogeneity, pH, viscosity, syneresis, spreadability, adhesion, and accelerated stability. The results showed that the ethanol extract of sappanwood has strong antioxidant activity with an IC50 value of 58.503 µg/mL. The SPF values ​​of the extract at concentrations of 500, 850, and 1000 ppm were 49.59; 46.64; and 45.86, respectively, which are included in the high protection category. The SPF value of the gel preparation ranged from 15.11 to 22.36, with formula F2 (0.85% extract and 1% Carbopol) producing the highest SPF value of 22.355 ± 0.085. All formulas met the physical quality requirements of topical preparations with a pH range of 4.59-4.91, viscosity of 122.8-283.7 P, spreadability of 4.40-5.38 cm, and adhesiveness of 4.3-4.6 seconds. The results of the study indicate that the ethanol extract of sappanwood has the potential to be developed as an active ingredient in natural sunscreen in the form of a stable, safe, and effective gel preparation.